2016
DOI: 10.1111/ctr.12860
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone use during cardiac transplant organ procurement

Abstract: Background Acute hypothyroidism after brain death results in hemodynamic impairments that limit availability of donor hearts. Thyroid hormone infusions can halt that process and lead to increased utilization of donor organs, but prolonged used of thyroid replacement has not been well studied. Methods We developed a 15 question survey regarding policies, procedures, and reporting of thyroid hormone use by OPOs. The survey was posted for five weeks on the Association of OPOs Portal. Results We received 29 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…Although this causes an increase in systemic vascular resistance, cardiac output is compromised by neurologic death-induced myocardial suppres sion and a decrease in thyroid hormone release owing to pitu itary failure. [8][9][10] This state has the potential to compromise trans plantation of the heart itself and other organs as a result of impaired perfusion. There is therefore a theoretical advantage to exogenous thyroid hormone supplementation.…”
Section: Thyroid Hormone Administrationmentioning
confidence: 99%
“…Although this causes an increase in systemic vascular resistance, cardiac output is compromised by neurologic death-induced myocardial suppres sion and a decrease in thyroid hormone release owing to pitu itary failure. [8][9][10] This state has the potential to compromise trans plantation of the heart itself and other organs as a result of impaired perfusion. There is therefore a theoretical advantage to exogenous thyroid hormone supplementation.…”
Section: Thyroid Hormone Administrationmentioning
confidence: 99%
“…Retrospective reviews of large national databases have suggested that those treated with thyroid hormone more often have hearts transplanted . A recent survey demonstrated that a majority of OPOs utilize thyroid hormone for all potential heart donors, while others reserve it for hemodynamically unstable donors . However, there remains little conclusive controlled evidence that such hormonal resuscitation improves shock, organ function, or rates of organ transplantation …”
Section: Introductionmentioning
confidence: 99%
“…There are conflicting data regarding the hormonal and hemodynamic collapse that can render organs not suitable for donation. 1 Ventricular contractility is reduced, associated with alterations in cardiac myosin fibers and changes to calcium channel function. Bradycardia may result from a decreased autonomic tone and a reduced chronotropic effect of thyroid hormone.…”
mentioning
confidence: 99%
“…Replacement of thyroid hormone can improve myocardial contractility and allow for a more accurate assessment of intrinsic cardiac function, minimize the use of potentially harmful vasopressors and inotropes, and may result in increased use of donor hearts that may not be accepted if cardiac function is assessed in the setting of hypothyroidism. 1 It has been suggested that hormonal resuscitation increases the availability of organs to be transplanted and results in less acute rejection and improved outcomes in the recipient. 10,11 What has remained unclear is whether there are benefits to continuation of thyroid hormone in the recipient after reperfusion of the transplanted heart.…”
mentioning
confidence: 99%
See 1 more Smart Citation